State and trait characteristics of attachment as predictors of outcome in inpatient psychotherapy - Jennissen, Simone; Volz, Matthias; Schauenburg, Henning; Dinger, Ulrike (Psychotherapy, 2024)
Attachment has mostly been investigated as a stable characteristic of individuals, although theoretical considerations and recent empirical findings suggest that attachment styles are also subject to change. When attachment is investigated as a treatment factor in psychotherapy, state and trait characteristics need to be differentiated, as they warrant different conclusions. This study examined the trait- and statelike characteristics of attachment styles over the course of inpatient psychotherapy as predictors of treatment outcome. A total of N = 419 patients provided weekly measurements of attachment styles and symptoms for up to 8 weeks of inpatient psychotherapy. Data were analyzed in multilevel longitudinal models controlling for rolling admissions and weekly changes in group membership. Over the course of treatment, patients’ attachment styles became more secure and less fearful-avoidant. Trait attachment security as well as gains in attachment security predicted better outcomes, while trait preoccupied and fearful-avoidant attachment as well as increases in attachment preoccupation and anxiety predicted worse outcomes. Findings imply that attachment security may grow during a relatively short inpatient treatment period and both trait attachment styles as well as changes in attachment styles predict outcome. (PsycInfo Database Record (c) 2024 APA, all rights reserved)